Developing Data Protection and Privacy Trends Reshaping the Business Landscape – the Case Study of Apple - Zając, Adrian (Zmiany w zakresie postrzegania prywatności przez użytkowników oraz przetwarzania danych osobowych przez organizacje – studium przypadku firmy Apple, 2023)
The global pandemic has significantly accelerated the transition of our lives into the digital world. However, with the change, many new threats connected with data protection and privacy have emerged. Due to the fact that many jurisdictions have no or basic privacy laws in place, their citizens are at risk of becoming targets of companies and malicious entities who wish to access their data. This article examines the significance of the data, tracking methods, the threats to the privacy and the response of governments worldwide by analysing various proposed or enforced laws. The main focus was placed on the growing awareness of the problem by users, and the implementation of various techniques and tools to limit data gathering by third-parties. The paper analyses how different forces in the environment are reshaping the business strategies of companies. The subject of the case study is Apple, which has introduced many privacy-related solutions that have affected the market and their competitors.
s. 146-162
Keywords: data protection; privacy; Apple; tracking; privacy paradox; ochrona danych; prywatność; śledzenie; paradoks prywatności